2014
DOI: 10.1021/ph4001108
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Improvement in Photogain and Speed of a Metal Oxide Nanowire Photodetector through Enhancing Surface Band Bending via Incorporating a Nanoscale Heterojunction

Abstract: The surface effect on the photodetection of metal oxide nanostructures acting as a double-edged sword achieves ultrahigh photogain but unavoidably prolongs the response time due to slow oxygen adsorption/desorption processes. In this study, we break the compromise to enhance the UV photogain by 3 orders of magnitude as well as increase the photoresponse speed by 5 times via incorporating opencircuit p−n nanoscale heterojunctions (NHJs) by forming single-crystalline p-NiO nanoparticles on n-ZnO nanowires. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 37 publications
(60 reference statements)
0
48
0
Order By: Relevance
“…[60a] In addition, they have reported that the photodetection properties of the device were improved significantly by decorating the ZnO nanowires with Au nanoparticles (Figure c) resulting in an ultralow dark current of 0.13 pA and I photo / I dark ratio of 5 × 10 6 (Figure d). Despite these excellent features, similar to the other ZnO‐based UV photodetectors, these devices exhibited a relatively slow response speed (25 s and 40 s rise time and 10 s and 300s decay time with and without Au decoration) due to the inherent defects, such as oxygen vacancies and zinc interstitials. [60a]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[60a] In addition, they have reported that the photodetection properties of the device were improved significantly by decorating the ZnO nanowires with Au nanoparticles (Figure c) resulting in an ultralow dark current of 0.13 pA and I photo / I dark ratio of 5 × 10 6 (Figure d). Despite these excellent features, similar to the other ZnO‐based UV photodetectors, these devices exhibited a relatively slow response speed (25 s and 40 s rise time and 10 s and 300s decay time with and without Au decoration) due to the inherent defects, such as oxygen vacancies and zinc interstitials. [60a]…”
Section: Methodsmentioning
confidence: 99%
“…The surface band bending establishes an internal electric field, which spatially separates photogenerated electron–holes leading to suppressed photocarrier recombination and dramatically prolonging carrier life‐times. [2d,3c,21] These effects are particularly prominent in nanocrystalline films, where the surface area is large and the depletion regions may extend throughout the entire film. [1b,2d,3c,9]…”
Section: Photodetection Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 By choosing, s 1 < s 2 , s 1 (s 2 ) is the shorter (longer) time constant corresponding to the faster (slower) process, which is ascribed to a bulk (surface) dominated process. Therefore, 1/s 2 and 1/s 1 are related to the surface oxygen readsorption/photodesorption rate and the bulk recombination rate, respectively.…”
Section: Effect Of Ultraviolet Illumination On Metal Oxide Resistive mentioning
confidence: 99%
“…For photodetector applications in particular, SBB enables remarkably high photoconductive gains (G), thanks to the spatial separation of photogenerated electrons and holes in the radial direction of nanowires, and significantly increased carrier lifetimes . The photodetector performance could be further improved under larger degrees of SBB, achieved via local Schottky, or p–n junctions at nanowire surfaces generated by decorating metal or metal oxide nanoparticles . Introducing polycrystallinity into nanowires also has proven beneficial since it creates band‐edge modulation along the nanowire axial direction, enabling high photodetector detectivity ( D *) and reduced dark currents ( I dark ) .…”
Section: Introductionmentioning
confidence: 99%